2019
DOI: 10.1007/s11420-018-09655-x
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Radiographs and Magnetic Resonance Imaging in Predicting Deltoid Ligament Ruptures in Ankle Fractures

Abstract: Background: Operative indications for supinationexternal rotation (SER) ankle fractures depend on the integrity of the medial structures. Despite the importance of assessing deep deltoid ligament injuries, the accuracy of common diagnostic tests has not been established. Questions/Purposes: The objective of this study was to compare the ability of injury (non-stress) and stress radiographs and magnetic resonance imaging (MRI) to diagnose deep deltoid ligament ruptures in operative SER ankle fractures. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…In contrast, Nortunen et al [33] would not recommend MRI for evaluating deltoid ligament integrity since only 54.1% of the patients who appeared to have a deltoid ligament rupture according to an MRI, actually had a rupture. Jeong et al [16] concluded that using MRI alone is inadequate to evaluate deltoid ligament ruptures, while the results of Warner et al [19] suggest that MRI is able to detect deltoid ligament rupture with sufficient certainty. However, the results of Warner et al [19] may be questioned since they only included surgically treated patients with SER-type ankle fractures, which may explain the high prevalence of deltoid ligament ruptures and, ultimately, influenced the sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Nortunen et al [33] would not recommend MRI for evaluating deltoid ligament integrity since only 54.1% of the patients who appeared to have a deltoid ligament rupture according to an MRI, actually had a rupture. Jeong et al [16] concluded that using MRI alone is inadequate to evaluate deltoid ligament ruptures, while the results of Warner et al [19] suggest that MRI is able to detect deltoid ligament rupture with sufficient certainty. However, the results of Warner et al [19] may be questioned since they only included surgically treated patients with SER-type ankle fractures, which may explain the high prevalence of deltoid ligament ruptures and, ultimately, influenced the sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [16] concluded that using MRI alone is inadequate to evaluate deltoid ligament ruptures, while the results of Warner et al [19] suggest that MRI is able to detect deltoid ligament rupture with sufficient certainty. However, the results of Warner et al [19] may be questioned since they only included surgically treated patients with SER-type ankle fractures, which may explain the high prevalence of deltoid ligament ruptures and, ultimately, influenced the sensitivity and specificity. The discrepancy between these two studies could also be explained by the fact that both studies did not use the same reference test.…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides details about the bony attachments of the different bands of DL, that could assist in the radiological diagnosis of DL injuries and advanced procedures related to its surgical repair and reconstruction. An MRI analysis, because of its increased accuracy, is a better diagnostic test for diagnosing deep deltoid rupture [31]. This study also offers a detailed approach for different band identification and isolation, using both gross observation and micro-dissection methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies using magnetic resonance imaging and intraoperative assessment to evaluate deep deltoid ligaments have suggested that MSV may overestimate the incidence of deltoid incompetence. 2,24 Further, Park et al 18 demonstrated that ankle position at the time of stress examination can influence the appearance of the MCS, suggesting that the test is subject to user error.…”
Section: Discussionmentioning
confidence: 99%